2021
DOI: 10.1051/0004-6361/202140591
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic helicity and energy budget around large confined and eruptive solar flares

Abstract: Context. In order to better understand the underlying processes and prerequisites for solar activity, it is essential to study the time evolution of the coronal magnetic field of solar active regions (ARs) associated with flare activity. Aims. We investigate the coronal magnetic energy and helicity budgets of ten solar ARs around the times of large flares. In particular, we are interested in a possible relation of the derived quantities to the particular type of the flares that the AR produces, namely, whether… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 72 publications
7
44
0
Order By: Relevance
“…For NOAA AR 12673, which produced the largest X-class flare of solar cycle 24, found that the helicity ratio increased and then relaxed to lower values before and after, respectively, each of the two major X2. Another follow-up study of Gupta et al [2021], with a set of 10 different NOAA-numbered AR samples, shows results supporting that the helicity ratio has a strong ability to indicate the eruptive potential of an AR, albeit with a few exceptions. A further statistical study with more samples is needed.…”
Section: Practical Applications 141 Temporal Variationmentioning
confidence: 89%
“…For NOAA AR 12673, which produced the largest X-class flare of solar cycle 24, found that the helicity ratio increased and then relaxed to lower values before and after, respectively, each of the two major X2. Another follow-up study of Gupta et al [2021], with a set of 10 different NOAA-numbered AR samples, shows results supporting that the helicity ratio has a strong ability to indicate the eruptive potential of an AR, albeit with a few exceptions. A further statistical study with more samples is needed.…”
Section: Practical Applications 141 Temporal Variationmentioning
confidence: 89%
“…The idea of the new parameter α/Φ AR can be generalized to "relative non-potentiality", which refers to the ratio of magnetic flux (or other physical quantities) in a flux rope to that in the surrounding magnetic structures (Lin et al 2021). A larger relative non-potentiality indicates a higher probability for a flux rope to erupt Thalmann et al 2019;Gupta et al 2021). Recently, Lin et al (2020) proposed a new relative non-potentiality parameter of the magnetic flux in the highly twisted region relative to its ambient background fields, which demonstrated a moderate ability in discriminating between confined and ejective events.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is suggested that eruptive flares tend to occur if the overlying background magnetic fields are weaker or more quickly decay with height (Török & Kliem 2005;Wang & Zhang 2007;Wang et al 2017;Baumgartner et al 2018;Amari et al 2018;Jing et al 2018;Duan et al 2019). Moreover, the magnetic non-potentiality of ARs is thought to be another important factor governing the eruptive character of solar flares (Nindos & Andrews 2004;Liu et al 2016;Cui et al 2018;Vasantharaju et al 2018;Thalmann et al 2019;Avallone & Sun 2020;Gupta et al 2021), such as free magnetic energy, relative helicity, magnetic twists, etc. Statistical studies have shown that CME productivity is correlated with the twist parameter α (Falconer et al 2002(Falconer et al , 2006, which characterizes the degree to which the photospheric magnetic fields of an AR deviate from a potential field (Leka & Skumanich 1999;Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For our study, we select three out of the ten ARs analyzed in Gupta et al (2021), namely NOAAs 11158, 11429, and 12673, which hosted the top four solar flares (in terms of peak soft Xray flux) during solar cycle 24 that occurred within ±35 • of the central meridian (see Table 1). The time window for analysis is chosen as in Gupta et al (2021), that is, it covers a time interval of several hours around the occurrence of the X-class flares, as is the time cadence (a 12min time cadence within ±1h around the flare peak time and a 1h cadence otherwise). Data possibly available during the impulsive phases of the flares were not considered due to the limited validity of the force-free assumption during eruptive processes.…”
Section: Active Region Selectionmentioning
confidence: 99%
“…We use time series of vector magnetic field data as originally prepared by Gupta et al (2021), who use hmi.sharp_CEA_720s…”
Section: Vector Magnetic Field Datamentioning
confidence: 99%